PENINGKATAN KEBIASAAN MANDIRI SISWA MELALUI KEGIATAN RUTIN DI SDN CIPICUNG - Firda Halawati; Ahmad Surais; Muhammad Sahlan Rizqi; Enung Nur'Aisah (Universitas Islam Al-Ihya Kuningan, 2024)
One of the focuses of KKN activities is improving the quality of education in the surrounding environment. Routine activities carried out during KKN, especially in the educational environment, one of which is at SDN Cipicung includes: (1) Flag Ceremony on Monday, (2) Reading Literacy on Tuesday and Wednesday, (3) Fatonah (Memorization) on Thursday, (4) Yasinan on Friday, and (5) Sports on Saturday. These activities are designed to familiarize students with routines that can support their independent learning. The results of observations show that routine activities at SDN Cipicung have a positive impact on improving students' independent learning habits. Students show increased self-discipline, responsibility, and good learning habits. This article concludes that routine activities carried out at SDN Cipicung can be a model in developing educational practices that support students' independent learning